BREEDING BUFFALOES IN GENOMICS ERA - ISSUES OF RECORDING AND EVALUATION - M. S. Khan; M. S. Rehman; F. Hassan (Journal of Animal and Plant Sciences, 2012)
Animal breeding is a very challenging discipline. Developments in the science of genomics are changing the face of animal breeding. While genomes of many farm animal species have either been sequenced or are in process of being sequenced, commercial companies are competing for efficiency and new innovations are being claimed every day. The DNA extracted from blood, hair or semen is genotyped for thousands of genetic markers (Single Nucleotide Polymorphisms). These represent places on the chromosomes where animals differ in the four nucleotides. With enough SNPs, association between SNP allele and quantitative alleles gives useful information for genetic evaluations. Thus estimating the genetic merit of an animal by assessing its own genetic make-up besides its own or relative’s actual performance is becoming common. It is being suggested that the genomic evaluations will revolutionize breeding programs and the traditional progeny testing programs will change or may even become obsolete. Presently, SNP chips are being used for some of the Bos taurus dairy cattle breeds such as Holsteins and efforts are underway for other breeds to include more reference populations. Buffaloes on the other hand, are mainly raised in the developing world where capacities of the institutions for such science are limited. We have a long way to go to harvest any benefit fromadvancements in genomics. Reference populations will be needed to use such technologies in buffaloes and authentic performance and pedigree recording will be fundamental in these efforts. Progress in genomics and issues of implementing such a recording and genetic evaluation program in Pakistan are reviewed in this paper.
Keywords: buffalo; milk; genomics; recording